A study of displacement in Jean Rhys' novel Wide Sargasso Sea - Che Jamal, Inna Malissa; Jujar Singh, Hardev Kaur; Mani, Manimangai (Australian International Academic Centre, 2014)
Wide Sargasso Sea, by Jean Rhys, is a novel filled with tragedy; two characters in conflict meet in circumstances not in their best interests but rather for other people. This novel is an illustration of the mad woman in the novel Jane Eyre, by Charlotte Bronte, as the story of her life before madness is told in the novel Wide Sargasso Sea. This study attempts to elucidate reasons for the feelings of displacement that the Western husband faces during his stay in the Caribbean, and also to discover to what extent the situation contribute to the oppression faced by Antoinette and imposed on her by her Western husband. There are many concepts amongst the theory of post-colonialism, e.g. otherness, hybridity, and (double) alienation. This research’s approach differs slightly from some previous research that has been done on this novel, as it focuses on the husband of Antoinette as the victim.